The Hoff circuit test is more specific than an incremental treadmill test to assess endurance with the ball in youth soccer players - Zagatto, A. M.; Papoti, M.; da Silva, A. S. R.; Barbieri, R. A.; Campos, E. Z.; Ferreira, E. C.; Loures, J. P.; Chamari, K. (Biology of Sport, 2016)
The assessment of aerobic endurance is important for training prescription in soccer, and is usually measured by straight running without the ball on a track or treadmill. Due to the ball control and technical demands during a specific soccer test, the running speeds are likely to be lower compared to a continuous incremental test. The aim of the present study was to compare the heart rate (HR), rating of perceived exertion (RPE) and speeds corresponding to 2.0 mmol·L-1, 3.5 mmol·L-1, lactate threshold (Dmax method) and peak lactate determined in the laboratory and in the Hoff circuit soccer-specific test. Sixteen soccer players (16±1 years) underwent two incremental tests (laboratory and Hoff circuit tests). The speeds were significantly higher in the treadmill test than on the Hoff circuit (2.0 mmol·L-1: 9.5±1.2 and 8.1±1.0 km·h-1; 3.5 mmol·L-1: 12.0±1.2 and 10.2±1.1 km·h-1; Dmax: 11.4±1.4 and 9.3±0.4 km·h-1; peak lactate: 14.9±1.6 and 10.9±0.8 km·h-1). The HR corresponding to 3.5 mmol·L-1 was significantly higher on the Hoff circuit compared to the laboratory test (187.5±18.0 and 178.2±17.6 bpm, respectively; P <0.001), while the RPE at the last incremental stage was lower on the Hoff circuit (P<0.01). The speeds during the Hoff specific soccer test and the HR corresponding to 2.0 mmol·L-1, 3.5 mmol·L-1 and Dmax/threshold were different compared with the laboratory test. The present study shows that it is possible to assess submaximal endurance related variables specifically in soccer players.